Studies of ion-surface interactions using multiphoton ionization - Wang, L.; Nor, R.; Mouncey, S.P.; Graham, W.G. (1992)
A experimental setup has been built for the study of low energy reactive ion interactions with surfaces. Particular emphasis is placed on the detection of the neutral material leaving the surface using nonresonant multiphoton.ionization. Some preliminary measurements show the suitability of the system for the proposed study.